Sustainable development and human rights - Nabi, Mohamed Amine (Journal of Human Sciences, 2021)
Since the establishment of the United Nations as an international body striving to maintain peace and security in the world on October 24, 1945, the international community has realized that this will not happen unless there is a kind of balance between protecting human rights on the one hand, and achieving continuous and sustainable human development on the other hand, The relationship between these two factors has begun to take new curves that touched many areas, and the concept of sustainable development has become primarily based at the present time on the fulfillment of the condition of guaranteeing basic human rights.